Riwayat Pengobatan, Efek Samping Obat dan Penyakit Penyerta Pasien Tuberkulosis Paru Terhadap Tingkat Kepatuhan Berobat - Puji Astuti Wiratmo; Widanarti Setyaningsih; Fitriani (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2021)
Introduction: Tuberculosis requires long-term treatment to achieve a cure. This type of long-term treatment causes patients to be non-adherent in undergoing treatment. Adherence to taking medication is a key factor in the success of treatment. Several patients discontinue treatment before completion for various reasons. Meanwhile, the characteristics related to the level of adherence to taking pulmonary TB drugs at the Cengkareng District Health Center have not been identified. Objective: The purpose of this study was to determine the relationship between treatment history, drug side effects, and disease history on TB treatment adherence at the Cengkareng District Health Center. Method: This study used a cross-sectional analytic observation design with 170 respondents through a judgmental sampling technique. The research instrument used secondary data from medical records to obtain medical history data, drug side effects, and comorbidities. Meanwhile, to measure the level of compliance used a questionnaire that has been tested for validity and reliability with a Cronbach Alpha value of 0.789. Data analysis was using Chi-square. Results and discussion: The results showed that there was no relationship between medication history and adherence to TB treatment with a p-value of 0.722. Meanwhile, there is a relationship between drug side effects and comorbidities with the level of adherence to TB treatment with p-values ​​of 0.002 and p-0.001. Conclusion: It is necessary to strengthen the role of community health workers in the role of education and monitoring of TB patient treatment together with patients and families so that TB treatment can be carried out. carried out to completion